Sarcopenia and mortality among a population‐based sample of community‐dwelling older adults. Issue 3 (15th October 2015) - Brown, Justin C.; Harhay, Michael O.; Harhay, Meera N.
Abstract: Background: Sarcopenia is a risk‐factor for all‐cause mortality among older adults, but it is unknown if sarcopenia predisposes older adults to specific causes of death. Further, it is unknown if the prognostic role of sarcopenia differs between males and females, and obese and non‐obese individuals. Methods: A population‐based cohort study among 4425 older adults from the Third National Health and Nutrition Survey (1988–1994). Muscle mass was quantified using bioimpedance analysis, and muscle function was quantified using gait speed. Multivariable‐adjusted Cox regression analysis examined the relationship between sarcopenia and mortality outcomes. Results: The mean age of study participants was 70.1 years. The prevalence of sarcopenia was 36.5%. Sarcopenia associated with an increased risk of all‐cause mortality [hazard ratio (HR): 1.29 (95% confidence interval (95% CI): 1.13–1.47); P < 0.001] among males and females. Sarcopenia associated with an increased risk of cardiovascular‐specific mortality among females [HR: 1.61 (95% CI: 1.22–2.12); P = 0.001], but not among males [HR: 1.07 (95% CI: 0.81–1.40; P = .643); P interaction = 0.079]. Sarcopenia was not associated with cancer‐specific mortality among males and females [HR: 1.07 (95% CI: 0.78–1.89); P = 0.672]. Sarcopenia associated with an increased risk of mortality from other causes (i.e. non‐cardiovascular and non‐cancer) among males and females [HR: 1.32 (95% CI: 1.07–1.62); P = 0.008]. Obesity, defined using body mass index ( P interaction = 0.817) or waist circumference ( P interaction = 0.219) did not modify the relationship between sarcopenia and all‐cause mortality. Conclusions: Sarcopenia is a prevalent syndrome that is associated with premature mortality among community‐dwelling older adults. The prognostic value of sarcopenia may vary by cause‐specific mortality and differ between males and females.